The physical rehabilitation in Yateritas community for elder people suffering from arthrosis - Marides Gómez-Noa (Universidad de Guantánamo, 2014)
The practical contribution of this investigation establishes the insertion of an innovative system of physical exercises intended to decrease the symptoms produced by the disease arthrosis in sick elders (inflammation and pain, appearing of deformities and decrease of the amplitude of movements in the articulations) which they can develop at home with their own resources and materials. The designed system of exercises constitutes an important instrument for the professionals in Yateritas who take care of the communal work addressed to decreasing the symptoms produced by arthrosis in the community's elder people in the San Antonio del Sur municipality.